Effectiveness of a blended learning intervention in cardiac physiotherapy. A randomized controlled trial - Marques-Sule, Elena; Sánchez-González, Juan Luis; Carrasco, Juan J.; Pérez-Alenda, Sofía; Sentandreu-Mañó, Trinidad; Moreno-Segura, Noemí; Cezón-Serrano, Natalia; Ruiz de Viñaspre-Hernández, Regina; Juárez-Vela, Raúl; Muñoz-Gómez, Elena (Frontiers in Public Health, 2023)
Background Blended learning (BL) combines both face-to-face learning (FL) and online learning. This study aims to compare the effectiveness of a BL intervention vs. a FL intervention in relation to the knowledge, competencies, satisfaction, perceptions, usability, and BL acceptance of physiotherapy students. Methods An assessor-blinded randomized trial was performed. A total of 100 students were randomly allocated to either the BL group (BLG, n = 48) or FL group (FLG, n = 52). The BLG received face-to-face classes plus access to online resources (online syllabus, Moodle, scientific-based videos and websites, activities, glossary, and apps). The FLG received face-to-face classes and hardcopy resources (hardcopy syllabus, scientific-based information, activities, and a glossary). Knowledge, ethical and gender competencies, satisfaction, perceptions, usability, and BL acceptance were assessed. Results The BLG showed higher scores than the FLG for knowledge (p = 0.011), three ethical/gender competencies (p < 0.05), increased motivation to prepare themselves before class (p = 0.005), increased motivation and ability of thinking (p = 0.005), improved understanding of important topics (p = 0.015), course organization (p = 0.017), educational material (p = 0.001), easiness of understanding (p = 0.007), comprehensive coverage of the subject (p = 0.001), and clarity of instructions (p = 0.004), while usability was acceptable. Conclusion The BL intervention can be used for improving the knowledge, competencies, perceptions, and satisfaction of the students. In addition, BL acceptance was positive, and usability was found to be acceptable. This study supports the use of BL as a pedagogical approach to foster innovative learning.